2006
DOI: 10.1590/s1806-83242006000300003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative therapeutic use of Risedronate and Calcarea phosphorica - allopathy versus homeopathy - in bone repair in castrated rats

Abstract: Comparative therapeutic use of Risedronate and Calcarea phosphorica -allopathy versus homeopathy -in bone repair in castrated ratsComparação do uso terapêutico de Risedronato e Calcarea phosphorica -alopatia versus homeopatia -no reparo ósseo em ratos castrados Cristina Werkman* Giselle Segnini Senra* Rosilene Fernandes da Rocha** Adriana Aigotti Haberbeck Brandão*** ABSTRACT: Osteoporosis, a disease characterized by progressive bone loss, has been the target of several studies in the past few years. It result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that plain radiographs are poorly correlated with fusion in animal models 6,27,45) . Also, fusion mass evaluation through optical density analysis does not faithfully describe the bone callus' morphological course because it does not consider the differences between the trabecular and lamellar bones and also because it adds the fibrous connective tissue to the measurements 42) . Therefore, we can conclude that radiographic evaluation is not an exact and sufficient method to assess a solid fusion versus a pseudarthrosis in an animal model fusion assessment 4) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that plain radiographs are poorly correlated with fusion in animal models 6,27,45) . Also, fusion mass evaluation through optical density analysis does not faithfully describe the bone callus' morphological course because it does not consider the differences between the trabecular and lamellar bones and also because it adds the fibrous connective tissue to the measurements 42) . Therefore, we can conclude that radiographic evaluation is not an exact and sufficient method to assess a solid fusion versus a pseudarthrosis in an animal model fusion assessment 4) .…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates are being used widely in diseases that present increase in bone resorption, such as senile or postmenapause osteopenia and osteoporosis 11,26,43,47) . Studies indicate that they stimulate a higher bone density increase than other drugs used with the same purpose, such as raloxifene or calcitonin 42) . Chemically, bisphosphonates are synthetic analogs of endogenous pyrophosphate 2,28) .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 But our general overview reveals an important common feature of the reviewed models: the effect of high dilutions is often to restore living systems to a certain 'stable state'. This is seen in studies of behavior, tissue organization and infection 13,14,20,[23][24][25] and in some cases demonstrated by mathematical models. 26,27 By the concept of 'stable state' we mean the recovery of a biological system to control or normal parameters, after some kind of physiological perturbation.…”
Section: Conceptual Aspectsmentioning
confidence: 96%
“…Tissue organization: Werkman and colleagues compared Calcarea phosphorica 6cH and Sodium risedronate (1 mg/ kg) in bone regeneration in a rat osteoporosis model. 25 Serial digital histomorphometric analysis of bones showed quantitative but, mainly qualitative differences between treatments and between treated and control rats. In osteoporotic bones, the osseous turnover is inadequate because, bone formation is diminished and resorption increased.…”
Section: Conceptual Aspectsmentioning
confidence: 98%
“…Orchidectomy has been used in orthopedic animal research to model male osteoporosis, but few studies have explored its use in the context of fracture healing. In these studies, osteoporosis was successfully induced by orchidectomy in rats age 2–8 months, 1–3 months before fracture 18‐20 . The orchidectomy technique has been described in detail elsewhere 16 …”
Section: Current Modelsmentioning
confidence: 99%